2003
DOI: 10.1042/ba20030012
|View full text |Cite
|
Sign up to set email alerts
|

The influence of physico‐chemical and process conditions on the physical stability of plasmid DNA complexes using response surface methodology

Abstract: Research is progressing fast to find safe and effective methods of delivering therapeutic genes to patients afflicted with a range of genetic and acquired diseases that either do not respond at all, or respond poorly, to treatment with small-molecule drugs or protein-replacement therapy. A technical barrier that remains relates to the need for scalable operations that can consistently and reproducibly make large quantities of the therapeutic gene vectors under the current Good Manufacturing Practice ('cGMP'). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The first reported study regarding this topic aimed to demonstrate the utility of central composite design in modeling responses such as vector size, zeta potential and transfection efficiency of several non-viral gene delivery vectors (Birchall et al, 2001). Similarly other authors have verified the effect of several parameters and their interaction on physical stability of polyplexes (Gazori et al, 2009;Mount et al, 2003;Zhong et al, 2007). Regarding electroporation, and to our knowledge there is no reported study aiming at multivariate optimising procedure for in vitro gene delivery to human MSC, mainly considering cell recoveries or yield of transfection as output values.…”
Section: Introductionmentioning
confidence: 97%
“…The first reported study regarding this topic aimed to demonstrate the utility of central composite design in modeling responses such as vector size, zeta potential and transfection efficiency of several non-viral gene delivery vectors (Birchall et al, 2001). Similarly other authors have verified the effect of several parameters and their interaction on physical stability of polyplexes (Gazori et al, 2009;Mount et al, 2003;Zhong et al, 2007). Regarding electroporation, and to our knowledge there is no reported study aiming at multivariate optimising procedure for in vitro gene delivery to human MSC, mainly considering cell recoveries or yield of transfection as output values.…”
Section: Introductionmentioning
confidence: 97%
“…A new quality in the mechanistic investigations of the colloidal properties of polycation–DNA vectors has been introduced by Lee et al [24,25], Sarkar et al [26] and Mount et al [27]. These authors have impressively demonstrated the aggregation kinetics of polycation–DNA complexes, mainly polylysine–DNA or liposome/polylysine–DNA complexes.…”
Section: Discussionmentioning
confidence: 99%
“…As the concentration of NaCl increases, the binding affinity of routine cationic polymers (PEI, chitosan, PLL) for DNA decreases and a salt induced aggregation may occur. This kind of aggregation is a consequence of the decrease in the repulsive electrical double layer (Debye-Huckel length) around the already-formed cationic complexes particles and occurs rapidly after mixing of the DNA solution and the cationic agent [20,[35][36][37]. Even a very little amount of NaCl solution added into the PDMAEMA 100 /DNA complex can induce rapid increase in absorbance of solution as shown in Fig.…”
Section: Journal Of Biomaterials Science Polymer Edition 337mentioning
confidence: 93%